Topical issues of the aquatic ecosystems bioindication: Russian experience and prospects - Timur E. Pavluk (Водное хозяйство России: проблемы, технологии, управление)
Methods of the aquatic ecosystems state bio/indication by macro/zoo/benthos sufficiently objectively indicate the degree of the pollutants and other critical economic activities’ negative impact upon water bodies. The range of currently available methods of bio/indication is rather wide; however, not all of them equally objectively and effectively produce assessment of aquatic system transformations. This article presents integrated analysis of the bio/indication methods of different principles and assessment criteria, and it gives rating of their popularity and effectiveness.